Classification of residential land uses in Hindiya using (GIS) - Aljanabi, Fouad Chead mutter (Al-Adab Journal, 2022)
The study examined the classification of residential land uses in the district of Hindia using geographical information systems. It is important to clarify the spatial space occupied by this use in the study area. It reflects the spatial distribution of residential units and the knowledge of any residential areas with high or medium density or low the construction of these units, the degree of proximity or proximity, the area of the residential plot and the density and percentage of occupancy of the residential unit, depending on the ARC GIS10.8 program in the representation and classification of the cartographic.The study reached a number of conclusions and recommendations that most of the residential neighborhoods in the study area are densely populated due to the existence of large areas are not invested as modern neighborhoods and some of them were agricultural land and were used as residential neighborhoods or residential stores, which registered the highest percentage of public housing density, Within the central commercial area, the majority of these shops came in the smallest area of residential plots, as they are not more than (100 m2). The residential neighborhoods are mostly (200-300 m2) except for Al Muthanna neighborhood. The area of residential plots is 600 m2. Remote sensing and geographic information systems are important in shortening the time, effort and cost that were required by the traditional mapping process and the possibility of modernizing it easily, as well as encouraging the use of geographic information systems throughout the State.